Agriculture MSMEs Sustainability Farmers Exchange Rates in Indonesia During the Covid-19 Pandemic and Farmer Empowerment Solutions - Jajang Supriatna; Djumarno Djumarno; Ahmad Badawy Saluy; Deden Kurniawan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In